Cultural shifts in Lombok: During and after the COVID-19 pandemic - Muhlisin Muhlisin; Ni Ketut Putri Nila Sudewi (Rainbow : Journal of Literature, Linguistics and Culture Studies, 2023)
The COVID-19 outbreak had various impacts on human lives. The COVID-19 pandemic affected economic activities, social life, and culture, leading people to adapt to new rules and circumstances. This study aims to identify cultural activities in Lombok, such as Nyongkolan, Begibung, and Maulidan that were impacted by the COVID-19 pandemic and to analyze the pattern of their changes. This study employs a qualitative descriptive method. This study employs various data collection techniques, including observation, interviews, and questionnaires. The findings suggest that cultural activities have temporarily shifted to adhere to government instructions aimed at mitigating the spread of COVID-19. After the pandemic COVID-19 ends, these cultural activities are conducted in the same way as before the pandemic. However, a small number of community groups still carry out the culture of Begibung as it was during the pandemic COVID-19 on the grounds that the modifications they applied during the pandemic are more effective and efficient, so it is good to be maintained while not eliminating the essence of the Begibung itself.